2020
DOI: 10.1128/jvi.01567-19
|View full text |Cite
|
Sign up to set email alerts
|

Modified Sialic Acids on Mucus and Erythrocytes Inhibit Influenza A Virus Hemagglutinin and Neuraminidase Functions

Abstract: Sialic acids (Sia) are the primary receptors for influenza viruses and are widely displayed on cell surfaces and in secreted mucus. Sia may be present in variant forms that include O-acetyl modifications at C-4, C-7, C-8, and C-9 positions and N-acetyl or N-glycolyl at C-5. They can also vary in their linkages, including α2-3 or α2-6 linkages. Here, we analyze the distribution of modified Sia in cells and tissues of wild-type mice or in mice lacking CMP-N-acetylneuraminic acid hydroxylase (CMAH) enzyme, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 91 publications
2
46
0
Order By: Relevance
“…Similarly, we found that WT H1, H2, and H4 HAs bind chicken, but not horse, erythrocytes in the hemagglutination assay (S2 Fig). Contrarily, we observed that WT avian H7 HAs bound both chicken (NeuAc [7,8]) and horse (mainly NeuGc [11,13,14]) erythrocytes and tracheal tissue while binding specifically to NeuAc on the glycan microarray. This distinguishes these H7 viruses from other subtypes of influenza A.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Similarly, we found that WT H1, H2, and H4 HAs bind chicken, but not horse, erythrocytes in the hemagglutination assay (S2 Fig). Contrarily, we observed that WT avian H7 HAs bound both chicken (NeuAc [7,8]) and horse (mainly NeuGc [11,13,14]) erythrocytes and tracheal tissue while binding specifically to NeuAc on the glycan microarray. This distinguishes these H7 viruses from other subtypes of influenza A.…”
Section: Discussionmentioning
confidence: 69%
“…This distinguishes these H7 viruses from other subtypes of influenza A. Possibly, the presence of NeuAc on horse erythrocytes and tracheal tissue, although estimated to be less than 10% of the total sialic acids [11,13,14], is sufficient to be bound by the WT avian H7 HAs. Additionally, the residual NeuAc-binding of the mutant avian H7 HAs may explain the binding to chicken erythrocytes and tissue.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While HA mediates virion-SA attachment and fusion, NA is responsible for terminal SA residues cleavage [19]. N-glycolyl and O-acetyl modification of SA could reduce binding affinities of both NA and HA [20]. In addition, NA possesses at least two calcium binding sites [21].…”
Section: Iav Viral Proteinsmentioning
confidence: 99%